Reactivated normal-sense shear zones in the core of the Greater Himalayan Sequence, Solukhumbu District, Nepal - Hubbard, Mary; Lageson, David R.; Bhattarai, Roshan Raj (Journal of Nepal Geological Society, 2017)
We present preliminary observations from the Solukhumbu region of Nepal, coupled with structures described in the literature, to suggest the importance of structural and metamorphic discontinuities within the Himalayan metamorphic core (Greater Himalayan Sequence) and reactivation of at least one of these thrust discontinuities with a normal (down-to-the-north) sense of displacement. Based on preliminary geochronologic data, development of these discontinuities may have evolved over time. In the Dudh Kosi Valley near Ghat, gneissic rocks and pegmatites exhibit tectonized fabrics and yield argon cooling ages of 4 Ma for K-feldspar and 9 Ma for biotite. Just north of Khumjung there is a prominent topographic break from which sheared gneissic rocks indicate a top-to-the-north, or normal, sense of shear. Near Pangboche, a repeated section of kyanitebearing rocks interleaved with sillimanite-muscovite schist suggests structural imbrication and/or interleaved retrograde metamorphism. Below the peaks of Nuptse and Lhotse, the Khumbu thrust (Searle 1999) appears to form the floor of a thick succession of leucogranite sills. We suggest that these discontinuities were formed over time, possibly from early MCT and STDS deformation at 21 Ma to as recent as 4 Ma, and need to be considered in kinematic models that combine channel flow with critical taper and tectonic denudation. Moreover, orogenic collapse in the Himalayan core may be migrating southward through time as the orogenic wedge continues to uplift in response to underthrusting of India and southward propagation of the Main Frontal Thrust system.